2010
DOI: 10.3109/15622970903447659
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic mechanisms in the modulation of the neurotrophin BDNF in the rat prefrontal cortex following acute agomelatine administration

Abstract: These data provide evidence that acute agomelatine treatment modulates the expression of BDNF through a functional interaction between melatonergic MT1/MT2 and serotonergic 5-HT(2C) receptors, supporting the notion that intracellular events can be regulated via a synergistic activity of different neuromodulatory systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 30 publications
2
41
0
2
Order By: Relevance
“…We have recently demonstrated that an acute injection of agomelatine can up-regulate the expression of BDNF messenger RNA (mRNA) levels in the prefrontal cortex through the functional interaction between melatonergic MT 1 /MT 2 and serotonergic 5-HT 2C receptors (Molteni et al 2010), thus preventing the circadian down-regulation of the neurotrophin.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently demonstrated that an acute injection of agomelatine can up-regulate the expression of BDNF messenger RNA (mRNA) levels in the prefrontal cortex through the functional interaction between melatonergic MT 1 /MT 2 and serotonergic 5-HT 2C receptors (Molteni et al 2010), thus preventing the circadian down-regulation of the neurotrophin.…”
Section: Introductionmentioning
confidence: 99%
“…7 Similarly, agomelatine produces an increase in gene expression of brain-derived neurotrophic factor (BDNF) in prefrontal cortex that is not reproduced with melatonin or 5-HT 2C antagonism alone. 8 Brain-derived neurotrophic factor has been implicated in depression and the response to antidepressant therapy. 9 However, the affinity of agomelatine for 5-HT 2C receptors is significantly lower than its ability to bind melatonin receptors.…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…Its mode of action may be explained by the synergy of MT 1 /MT 2 and 5-HT 2C receptors, which increases noradrenergic and dopaminergic neurotransmission, and a specific release of noradrenaline and dopamine has been described in the prefrontal cortex without effect on the extracellular levels of serotonin [3][4][5]. In addition, an increase of neurotrophic factors (e.g., brain-derived neurotrophic factor, BDNF) and a decrease in stress-related glutamate elevation have also been described [2,6,7] as well as resynchronization of circadian rhythms [8][9][10].…”
Section: Introductionmentioning
confidence: 99%